The Complete Guide to the Herschel Objects : Sir William Herschel's Star Clusters, Nebulae and Galaxies - Bratton, Mark, 1955- (Cambridge books online., 2011)
Provides a complete re-examination of Herschel's entire catalogue; a must-have for amateur astronomers seeking new and exciting observing challenges.